2020
DOI: 10.3892/ol.2020.11832
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑125b reduces glucose uptake in papillary thyroid carcinoma cells

Abstract: Previous studies have shown that microRNA (miR)-125b plays important roles in several human cancer types. The aim of the present study was to analyze the potential roles of miR-125b in papillary thyroid carcinoma (PTC). It was found that miR-125b was downregulated in PTC and its expression was affected by clinical stages. Glucose transporter 1 (GLUT1) was upregulated in PTC and was negatively correlated with miR-125b. In PTC cells, overexpression of miR-125b suppressed glucose uptake and downregulated GLUT1. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…The miR-185 in mice and diabetic patients is significantly downregulated, and this miRNA is associated with blood glucose [ 80 ]. The miR-125b can decrease glucose uptake and inhibit insulin signaling pathway [ 81 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The miR-185 in mice and diabetic patients is significantly downregulated, and this miRNA is associated with blood glucose [ 80 ]. The miR-125b can decrease glucose uptake and inhibit insulin signaling pathway [ 81 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…На культуре анапластического РЩЖ было показано, что экзогенная miR-125b снижает экспрессию киназ PI3K, p-AKT и p-mTOR в клетках [6]. Кроме того, выявлено, что микроРНК-125b влияет на метаболизм глюкозы, изменяя пролиферативную активность опухоли [7], а также на экспрессию рецепторов ростовых факторов [8] и транскрипционных факторов (NF-kB) [9], определяя метастатический и инвазивный потенциал опухоли [10]. Выявлена связь экспрессии miR-125b с наличием мутации BRAF V600E, определяющей агрессивные свойства опухоли [11].…”
Section: Abstract: Papillary Thyroid Cancer Hsa-mir-125b Tumor Invasi...unclassified
“…Известно, что опухолевая инвазия является неблагоприятным признаком заболевания, что связано с изменением внутриклеточной сигнализации, транскрипции, экспрессии факторов роста [6,7]. Перечисленные изменения способствуют формированию агрессивного фенотипа злокачественного новообразования.…”
Section: онкологияunclassified
“…Zhang et al confirmed that microRNA-125b can reduce glucose uptake in TC cells by downregulating GLUT1 expression, thus affecting the development and progression of cancer. 83 Due to these changes in TC, GLUT1 expression increases to compensate for the metabolic reprogramming so that enough glucose can be taken up to fulfill the needs of TC cells with high metabolism and elevated proliferative activities, and such changes in TC are associated with its growth, proliferation and progression. In summary, we can conclude that after the occurrence of TC, many factors in TC can promote GLUT1 expression, which further regulates the uptake of glucose through its own changes in expression and then affects the energy metabolism of cells to confront the needs of TC cells to maintain their growth, proliferation and progression.…”
Section: Glucose Transporters (Gluts) and Energy Metabolism In Tcmentioning
confidence: 99%